h THE IMPORTANCE AND ADVANTAGES OF LEARNING FOREIGN LANGUAGES: THE IMPORTANCE AND ADVANTAGES OF LEARNING FOREIGN LANGUAGES - Isokova, Maftuna (Журнал иностранных языков и лингвистики, 2022)
Introduction of methods of using modern pedagogical technologies in language learning. Study the advantages of studying in the globgangan world and the prospects of using foreign sources.